Dietary supplementation with Bacillus velezensis and Pichia guilliermondii improves growth performance through intestinal morphology and functionality enhancement in weaning piglets - Marcella Massimini; Gianmarco Del Vecchio; Francesca Ciaramellano; Isa Fusaro; Amilcare Barca; Mariarita Romanucci; Melania Giammarco; Chiara Amatetti; Benedetta Bachetti; Marco Di Domenico; Gianluca Nicolai; Barbara Secondini; et al. (PLoS ONE, 2025)
The post-weaning period in piglets is often associated with significant changes in intestinal structure and function, which can negatively affect growth and performance. This study aimed to evaluate the effects of dietary supplementations with prebiotics and/or probiotics on intestinal morphology and functionality during the post-weaning phase. Piglets were supplemented with different diets, including combinations of Pichia guilliermondii (prebiotic, PRE) and Bacillus velezensis (probiotic, PRO), and their growth performance, intestinal histology, and functionality were assessed. Growth performance was evaluated in the post-weaning period, with a notable improvement in weight gain observed in piglets receiving the combined prebiotic/probiotic supplementation. Morphometric analysis revealed significant differences in intestinal morphology, particularly in the small intestine. The PRE/PRO combination was most effective in improving villus size in the duodenum and ileum at early post-weaning stages, while the jejunum showed a greater sensitivity to weaning stress. Molecular analysis indicated diet-dependent changes in the expression of key markers involved in nutrient absorption and mucosal integrity, including SLC15A1 and TJP1 . Additionally, 16S rRNA sequencing revealed diet-related changes in gut microbiota composition where α-diversity and β-diversity increased independently of the diets and, specific beneficial taxa (e.g., Lachnospiraceae) were enriched in the supplemented groups. These microbial shifts were consistent with the improved mucosal thickness observed in the colon, suggesting a potential contribution of microbial modulation to epithelial integrity of the large intestine. Overall, the results suggest that the synbiotic supplementation of prebiotics and probiotics can enhance intestinal integrity in both the small and large intestine, promote growth, and improve overall gut health in post-weaning piglets.